Women who remain unmarried after their thirties in India - Pautunthang, N. (Universitas Trunojoyo Madura, 2024)
This study analyses the dynamics of never-married women aged 30 years and above in India over three periods: 2005-06, 2015-16 and 2019-21 based on different socio-demographic dimensions. It analyses never-married women in India and uses data from three rounds of the National Family Health Survey (NFHS). The analysis examines different variables of interest such as rural-urban differences, educational attainment, types of occupation and wealth index followed by religion and caste. The results are nuanced and capture the intricacies of broad national trends and regional dynamics. Of course, such an overarching trend masks wide regional variation. On one hand, it is the states like Jammu and Kashmir, Himachal Pradesh, Sikkim etc., where there has been prevalence of this trend showing an upward trend that marriage patterns are on change. On the other hand, states like Haryana and Bihar are showing a steady decrease which speaks about the effect of regional cultural dynamics. Moreover, the fluctuations in states like Meghalaya, and Assam reaffirm how multi-parameter is determining marital choices. The binary logistic regression used in the study analyses the effect of place of residence, education, occupation, wealth index, religion and caste on women’s chances to remain unmarried. The regression analysis demonstrates the distinct influences of these factors on marital status and yet they still only tell part of the story about an understudied subgroup, never-married women.